2023
DOI: 10.1021/acs.jpcc.3c00965
|View full text |Cite
|
Sign up to set email alerts
|

A First-Principles Investigation of the Driving Forces Defining the Selectivity of TiO2 Atomic Layer Deposition

Abstract: Area-selective deposition (ASD) is a technique to deposit material only on a defined area of a prepatterned surface, while no deposition occurs on adjacent surface areas. It is the subject of intense investigations by the scientific and engineering communities as it offers the prospect to simplify and improve patterning processes for fabrication of nanoelectronic devices as well as to reduce the manufacturing costs. Numerous efforts have been dedicated to identify process conditions for highly selective ASD pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…The higher selectivity of GST ALD compared to those of other ALD processes may be related to the lower temperature of the deposition. Presumably, the much lower temperature of the GST ALD process prevents thermal degradation of the TMS-terminated SiO 2 surface. , Unfortunately, we cannot investigate the impact of the temperature on GST ALD due to the narrow temperature window of the process (70–80 °C). Another hypothesis is that the precursor chemistry itself with the lack of H 2 O as a co-reagent could be responsible for achieving high selectivity for GST, similar to that proposed previously for TiO 2 ALD .…”
Section: Resultsmentioning
confidence: 99%
“…The higher selectivity of GST ALD compared to those of other ALD processes may be related to the lower temperature of the deposition. Presumably, the much lower temperature of the GST ALD process prevents thermal degradation of the TMS-terminated SiO 2 surface. , Unfortunately, we cannot investigate the impact of the temperature on GST ALD due to the narrow temperature window of the process (70–80 °C). Another hypothesis is that the precursor chemistry itself with the lack of H 2 O as a co-reagent could be responsible for achieving high selectivity for GST, similar to that proposed previously for TiO 2 ALD .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have aimed to enhance the adsorption selectivity of precursors in ASD processes through theoretical precursor screening using DFT. Activation ASD can be perceived as being similar to inherent ASD on the simulation scale, as it also induces reactivity differences in localized regions at the level of the activated molecule …”
Section: Predictions Of the Properties Of The As-ald Precursormentioning
confidence: 99%
“…plays an important role in the Au nucleation inhibition from the first-principles computations and in situ infrared spectroscopy. 19 The ALD reaction mechanisms of TiCl 4 , 20 (DFT) and thermodynamic calculations, and the surface termination plays an important role in the nucleation delay.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted to study the mechanism of ALD nucleation delay by performing theoretical simulation methods assisted in situ charaterizations. Hock et al resolve the nucleation delay and island growth of thermal ALD of gold on aluminum oxide by in situ quartz crystal microbalance, and it is found that surface chemistry (including the intermediates, volatile byproducts, etc.) plays an important role in the Au nucleation inhibition from the first-principles computations and in situ infrared spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation